Assessment and Treatment of Acute Low Back Pain: A Multidisciplinary Clinical Practice Guideline - Andrea C Skelly; Devan Kansagara; Jessica Oswald; Roger Chou; Daniel P Alford; James Babington; Andrew Chang; Beth Darnall; Mark Holtsman; Heather Jackson; Anthony Lisi; Tom Norris; et al. (Pain Medicine, 2026)
Abstract Purpose To create an evidence-based guideline for the evaluation and management of acute low back pain. Methods A multidisciplinary guideline development group formulated recommendations based on systematic review (PROSPERO Registration 537276) of evidence and using a protocol based on the Grading of Recommendation Assessment, Development, and Evaluation (GRADE) working group methodology. Intended users and settings Clinicians providing care to individuals presenting with acute low back pain (<6 weeks duration) with or without radiculopathy in outpatient settings.